2008
DOI: 10.1213/01.ane.0000278866.01963.79
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Combination of Epinephrine and Vasopressin with Lipid Emulsion in a Porcine Model of Asphyxial Cardiac Arrest After Intravenous Injection of Bupivacaine

Abstract: In this model of a bupivacaine-induced cardiac arrest, the vasopressor combination of vasopressin and epinephrine compared with lipid emulsion resulted in higher coronary perfusion pressure during CPR and survival rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 24 publications
2
64
0
1
Order By: Relevance
“…18,19 The incidence of systemic toxicity from local anesthetics appears to be decreasing with the use of safer local anesthetics 20,21 and the widespread introduction of procedural safety. 20 Since dextromethorphan and dextrorphan are better tolerated systemically than bupivacaine in this animal model, these drugs should be investigated further as possible useful local anesthetics in the clinical setting.…”
Section: áMinmentioning
confidence: 99%
“…18,19 The incidence of systemic toxicity from local anesthetics appears to be decreasing with the use of safer local anesthetics 20,21 and the widespread introduction of procedural safety. 20 Since dextromethorphan and dextrorphan are better tolerated systemically than bupivacaine in this animal model, these drugs should be investigated further as possible useful local anesthetics in the clinical setting.…”
Section: áMinmentioning
confidence: 99%
“…68,69 This approach has support from animal experiments. 70,71 2. Use of lipid rescue is effective and superior to vasopressor therapy in local anaesthetic toxicity.…”
Section: The Use Of Propofol For Lipid Rescuementioning
confidence: 99%
“…Mayr and colleagues observed that vasopressin or adrenaline or a combination of the two was successful while lipid emulsion alone was uniformly unsuccessful in effecting resuscitation in a porcine model of bupivacaine cardiotoxicity. 71 The explanation offered for the divergent successes of lipid versus vasopressor therapy focussed on study design. Mayr and colleagues introduced a period of apnoea after bupivacaine administration while in the Weinberg and Di Gregorio 66 studies hypoxia and delay in resuscitation were avoided.…”
Section: The Use Of Propofol For Lipid Rescuementioning
confidence: 99%
“…Due to their size, pigs better mimic the CPR-related aspects of drowning resuscitation and ICU care is feasible [234][235][236][237]. However, neuropathological targets and long-term outcome are not well defined.…”
Section: Pig Aca Modelsmentioning
confidence: 99%